1976
DOI: 10.1002/ps.2780070612
|View full text |Cite
|
Sign up to set email alerts
|

The mode of action of insecticides: Accelerated water loss and reduced respiration in insecticide‐treated Musca domestica L.

Abstract: Contact with organophosphorus, carbamate, organochlorine and pyrethroid insecticides caused accelerated water loss from all major parts of the integument of the housefly. The response appeared to be specific in that only insecticides, and not their truly non-toxic analogues, had this effect, specificity being also reflected in resistance and in synergistic and antagonistic responses. As an insecticide dispersed laterally in the integument the effect spread to more distant parts, including the intestinal and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…More interestingly, the current study revealed no significant decrease of weight in mosquitoes surviving after exposure to PPM and PM compared with control individuals, suggesting weight loss in dead samples as an indicator of insecticide activity in mosquito matrix. Insecticides can possess a dehydrating effect as it has been described for other insects and substances [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…More interestingly, the current study revealed no significant decrease of weight in mosquitoes surviving after exposure to PPM and PM compared with control individuals, suggesting weight loss in dead samples as an indicator of insecticide activity in mosquito matrix. Insecticides can possess a dehydrating effect as it has been described for other insects and substances [42, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Gerolt (1976) concluded that contact insecticides migrate through the spiracles into the tracheal system, where they penetrate through the thin cuticle. It was also suggested that an oil film covers the spiracles and respiration stops.…”
Section: Discussionmentioning
confidence: 99%
“…Any suggestion as to the site of the primary lesion must remain rather speculative at this stage but the outcome of recent work (Gerolt, 19766) opened the possibility that it could be integumental. Insecticides such as organophosphates, carbamates, organochlorines and pyrethroids were found to induce excessive water loss from all major parts of the integument, including that of the tracheal system, and it was postulated that this reaction may constitute the primary cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, immediately upon knockdown after application of the LD50 dose (5-15 min), AChE was inhibited by more than 80%. Effect of methomyl treatment on the water balance Many insecticides, including methomyl, induce water loss in insects (Gerolt, 19766), and this, presumably, could lead to increased sensitivity. The possibility was examined, therefore, whether flies treated with the sublethal dose of 0-05 /tg methomyl would be able to fully replenish the lost water before the second dose was applied after 24 h. The results obtained with 3 groups of 20 flies treated with an acetone solution of methomyl and with acetone alone were as follows: mean weight/fly just before and 24 h after treatment with methomyl 26-7 ± 0-5 mg and 26-9 ± 0-9 mg, respectively, and with acetone alone 26-2 ± 0-4 mg and 26-3 ± 1 -2 mg, respectively.…”
Section: Inhibition Of Ach Esterasementioning
confidence: 99%